Tetracycline versus penicillin in the treatment of louse-borne relapsing fever - Gebrehiwot, T; Fiseha, A (Ethiopian medical journal, 1992)
A prospective study of 120 louse-borne relapsing fever (LBRF) patient admitted to Mekele Regional Hospital, Tigray, Ethiopia from September to November 1991 was done. The patients were assigned systematically to a single dose of either tetracycline or procaine penicillin (sixty each). Doses given were oral tetracycline 250 mg or intramuscular procaine penicillin 200,000 units for children ages 12 years or less, and 500 mg or 600,000 IU for adults, respectively. The aim of this study was to compare the clinical effectiveness of tetracycline to that of procaine penicillin. Both drugs induced a Jarisch-Herxheimer (JH) like reaction, which was clinically similar in the two treatment groups, but peaked later and was more prolonged in the patients treated with procaine penicillin. Spirochaetes cleared more slowly and relapses were noticed only in the procaine penicillin treated group. Thus, tetracycline is recommended as first choice therapy and a single dose is sufficient for treatment of LBRF patients.